Reconquer Reconquista & the space of opportunities - Axelblom, Caroline; Wiström, Sophie (2019)
This study explores the narratives of the Reconquista’s river basin in the greater Buenos Aires Metropolitan Area, in particular the Morón River - the main polluter. The aim is to explore how to design counteractive narratives in regards to the current development. The method is partly derived from the Travelling Transect, a method developed by Lisa Diedrich, Gini Lee and Ellen Braae since 2013. The method is adjusted to fit the specific conditions concerning the river Reconquista.